Genotoxic effect of various forms of tobacco on oral buccal mucosa and nuclear changes as a biomarker - Sowmiya Devadoss; Murali Chinnakonda Raveendranath; T Shanmugam Kathiresan; Kesavan Ganesan (Wolters Kluwer Medknow Publications, 2021)
Aim: The present study aims to assess the genotoxic effect of various forms of tobacco users on buccal mucosa and nuclear changes as biomarkers. Materials and Methods: The study involves 150 cases, they were divided into three groups (two study groups and one control group). The buccal cytological smears were taken from three groups: Group I - 50 smokers, Group II - 50 nonsmokers (smokeless tobacco), and Group III - 50 control group. The buccal cells were transferred into a test tube containing Tris-ethylenediaminetetraacetic acid buffer (pH = 7) and was centrifuged (Remi® 1500 revolution/min [rpm]). Cell suspensions were transferred to the slides and fixed. The slides were stained using PAP and Feulgen stain. The MN and other nuclear abnormalities were studied and compared. Results: Nonsmokers (smokeless tobacco) had significantly increased frequency of all nuclear anomalies compared to smokers and healthy controls. Binucleation, karyorrhexis, micronuclei (MN), karyolysis, broken egg nuclei, and prominent nucleoli in nonsmokers (smokeless tobacco) and condensed chromatin in smokers were the most frequent anomalies. Binucleation and karyorrhexis were significantly more frequent in nonsmokers (smokeless tobacco) compared to smokers. The other nuclear abnormalities were not statistically significant in smokers and nonsmokers (smokeless tobacco). Conclusion: Numerous studies have stated that MN and other nuclear anomalies were present in higher frequency in smokers and nonsmokers. In our study, we found binucleation and karyorrhexis were statistically significant in nonsmokers (smokeless tobacco) compared to smokers. The other nuclear anomalies showed insignificant results. In order to further validate the significance of this study, a larger sample size has to be studied. On comparing the staining efficacy of smokers and nonsmokers using PAP and Feulgen stain, both the stains showed positive results. In the present study, DNA-specific Feulgen stain shows better staining of nuclear anomalies compared to DNA nonspecific PAP stain, which was found to be statistically significant.